Assessment of Pain and Analgesic Use in Children Following Otologic Surgery. (8th December 2020) - Benchetrit, Liliya; Kwock, Megan; Ronner, Evette A.; Goldstein, Sheli; Shu, Edina; Lee, Daniel J.; Mankarious, Leila A.; Caloway, Christen; Kempfle, Judith; Cohen, Michael S.
Abstract : Objective: To compare postoperative pain and analgesic use in children following transcanal endoscopic ear surgery (TEES) vs non–transcanal endoscopic ear surgery (non‐TEES). Study Design: Prospective case series. Setting: Tertiary care center. Methods: Surveys using the Wong‐Baker FACES Pain Rating Scale and recording the frequency and dosage of consumed analgesics were administered prospectively to caregivers of children undergoing otologic surgery between May 2018 to February 2020. Pain intensity and medication use were recorded twice daily for 6 days, starting on postoperative day 0. Mean pain scores and mean number of consumed analgesic doses were compared between groups. Results: Survey response rate was 57.9%. Among 53 patients who completed the survey, 35 (66.0%) underwent TEES and 18 (34.0%) underwent non‐TEES. Mean pain ratings on postoperative days 0 and 1 were significantly lower among children undergoing TEES (2.2 and 2.1) vs non‐TEES (4.0 and 4.1), P =. 045 and P =. 008, respectively (Mann‐Whitney U test). The mean pain ratings across the 6 days were similar in TEES (1.7) and non‐TEES (2.6) ( P =. 140, Mann‐Whitney U test). The mean number of analgesic doses consumed per half‐day over the 6 days was significantly lower among children undergoing TEES (0.3) vs non‐TEES (0.6; P =. 049, Mann‐Whitney U test). Conclusion: Postoperative pain following TEES and non‐TEES in children was overall low. Children undergoing TEES had a small but statistically significant decrease in pain on postoperative days 0 and 1 and decreased use of pain medications compared to non‐TEES.